Tensions Between Capitalism and Democracy Today From the Perspective of J. S. Mill and J. A. Schumpeter - Baş Dinar, Gülenay; Akdere, Çınla (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
XI, 124 p.